Variation in the diatom community under fast ice near Syowa Station, Antarctica, during the austral summer of 1997/98 - Ishikawa, Akira; Washiyama, Naoki; Tanimura, Atsushi; Fukuchi, Mitsuo (National Institute of Polar Research, 2001)
P(論文) Variations in abundance and community structure of diatoms under the fast ice near Syowa Station were investigated almost daily during the austral summer of 1997/98. Two periods of high chlorophyll a concentration were observed throughout the study : from the end of December to early January and from the middle to the end of January. Size fractionation of chlorophyll a revealed that phytoplankton during the former period consisted mostly of organisms larger than 20μm and during the latter period, 10-20μm. The large diatoms, Porosira pseudodenticulata and Pseudonitzschia turgiduloides, and small diatoms, Fragilariopsis spp., were the dominant organisms in the former and latter periods, respectively. Melting of the fast ice occurred in January, indicating a possibility that small sized diatoms were released from the ice to the water column. Accumulation of small diatoms in a sediment trap followed a decrease of their abundance in the water column. These results indicate that most of the ice algae detached from the ice sank directly to the bottom during the latter half of the austral summer. departmental bulletin paper